Banco de dados georreferenciado para apoio à gestão de trânsito em cidades de pequeno e médio portes - Vendrametto, Larissa Lenharo (2012)
The modernization of the cities has brought an improvement in the lives of the urban population, although the negative consequences weigh considerably. In any kind of transformation, the negative effects are not always considered and treated to abolish them or less minimize them. Traffic is a clear example of this fact. The significant increase in the fleet of vehicles has generated several urban problems such as high rates of occurrence and severity of traffic accidents, congestion and degradation of the urban environment, influencing the quality of life. With the enactment of the Brazilian Traffic Code (CTB) in 1988, municipalities assumed the responsibility to manage their traffic, adding to his responsibilities the authority to act in this area taking into account the interests and local peculiarities. In this sense, each municipality must municipalise directly assuming the powers specified in Article 24 of the CTB. However, municipalities have been reluctant to take charge of decentralization of traffic. According to data DENATRAN (2012), only 1,221 municipalities have effectively assumed the management of their traffic, which corresponds to 29% of 5,563 Brazilian municipalities. Many factors can be pointed as responsible for this reluctance, and one of them is the lack of knowledge of the reality of local traffic. It is important that the institutions, who are competent to intervene on the county road system and its maintenance, to know the dynamics of the space on which they intend to launch campaigns, a quality management includes the selection, acquisition, integration and use of information so systematized. The management and analysis of information associated with meaningful comparisons must adequately support the decision making process within the organization. Given this, the Geographic Information Systems - GIS become an effective tool and capable of helping the management, providing a modern and agile tool for specialized studies, with the recognition of the traffic situation as a whole. Therefore, this paper aims to contribute to the management of municipal public transit in cities small and medium-sized Brazilian, through the development of a tutorial to support the implementation of a geographic information system free - Free GIS, showing that it is not always necessary high investment amount for the production of quality information for management of a city road.